If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11x + 6 = -16 Reorder the terms: 6 + -11x = -16 Solving 6 + -11x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -11x = -16 + -6 Combine like terms: 6 + -6 = 0 0 + -11x = -16 + -6 -11x = -16 + -6 Combine like terms: -16 + -6 = -22 -11x = -22 Divide each side by '-11'. x = 2 Simplifying x = 2
| -484-1695= | | 8x^4-28x^3+6x-21= | | c+9=-8c | | 7x-9=7+5x | | 40-4n=-4(3n-4) | | 7n+10=5n | | 4x-(9x+3)=0 | | 2/3m-1n5 | | 2x+25+1=x+17 | | 6(x-2)-6=4x | | -361-(-58)= | | 12=x+5x-6 | | -10x-4x=-7 | | (X-1)(2x-2)= | | x-.60=.54 | | A+2a+3a+4a=180 | | -17+r=-3 | | -6a-6(1+4a)=-216 | | -24-1/8p=-3/8p | | x+(x*2)=1815 | | -191+(-511)= | | R+21=21+18r | | 5m^4-5=0 | | -2y+-3z= | | -24-1/8p=-3/8 | | 2(x+15)=(3x+20) | | 9h=5+8h | | -57+(-98)= | | (2m+8)(4m-3)= | | x^2+4bx-12b^2= | | 6p+3(p-1)=24 | | 2(12-8x)=x+11x |